ICT-based teaching aid materials in rural high school Additional Mathematics learning : needs analysis - Siti Seri Kartini Mohd Yatim; Salmiza Saleh; Hutkemri Zulnaidi (Penerbit Universiti Kebangsaan Malaysia, 2021)
The needs analysis phase is the initial phase of the study when information is collected from the context and environment that are to be studied. This paper discusses the findings of a needs analysis carried out as the first step in the construction of an Information and Communication Technology-based (ICT) teaching module. This paper presents the difficulty levels of Form 4 Additional Mathematics topics and the students’ motivation level in the subject of Additional Mathematics. A total of 147 students and 63 teachers of Additional Mathematics subject from 3 rural high schools in Kulim, Kedah were involved. This study used a quantitative method supported by a qualitative method. A questionnaire was administered to the respondents, followed by a semi-structured interview to collect data. Findings show that a majority of teachers and students suggested that the Differentiation topic as the most difficult topic for Form 4 Additional Mathematics subject, whereby students need ICT to understand the concept. Furthermore, this study discovered that teachers rarely use ICT and GeoGebra Software in teaching and learning (T&L) process. Based on the results, suggestions from teachers and students are taken into consideration for the beginning of the construction of an ICT module.